Genetic diversity and structure in two protected Posidonia oceanica meadows. (August 2015) - Micheli, Carla; D'Esposito, Daniela; Belmonte, Alessandro; Peirano, Andrea; Valiante, Luigi Maria; Procaccini, Gabriele
Abstract: Posidonia oceanica meadows growing along the west Mediterranean coastline are under continuous anthropogenic pressure. The way meadow health correlates with genetic and genotypic diversity in P. oceanica, is still under debate. Here we report a microsatellite analysis of two P. oceanica meadows living in protected areas of the Ligurian (Monterosso al Mare, MPA of "Cinque Terre") and central Tyrrhenian Sea (Santa Marinella, regional Site of Community Importance). Both meadows were recently classified as "disturbed", according to shoot density and other phenological parameters. Between the two meadows, Santa Marinella showed higher genetic diversity, while clear genetic substructure was present in both sites, reflecting high spatial heterogeneity. The present study suggests that genetic diversity does not match unequivocally with shoot density and leaf morphology and that small scale intra-meadow heterogeneity is an important factor to consider for establishing the relation between genetic/genotypic variability and health of natural seagrass meadows. Highlights: Posidonia oceanica shows different genetic diversity in two protected meadows. Demography and genetic traits are uncoupled in the two meadows. Posidonia oceanica shows heterozygosity excess. Genetic diversity shows enhanced small scale intra-meadow variability. Intra-meadow variability affects assessment of demography Vs genetics relationship.